Soft magnetic alloy powder and preparation method thereof, magnetic ring inductor and preparation method thereof
FeCuNbSiBP amorphous powder was prepared by air-sprayed water-cooled atomization and crystallization annealing treatment, which solved the problem of easy puncture of the insulating layer during the pressing of the soft magnetic composite material powder core, and prepared amorphous nanocrystalline soft magnetic field with excellent performance Alloy powder and magnetic ring inductors achieve improved spherical shape and density and improved soft magnetic properties.
Patent Information
- Application Number
- CN202010720769.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-07-24
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2040-07-24
AI Technical Summary
The existing soft magnetic composite materials are prone to piercing the insulating layer during the pressing of the powder core, resulting in sharp deterioration of soft magnetic properties, and there is a sharp edge problem in the preparation of amorphous nanocrystalline magnetic powder core.
The amorphous nanocrystalline FeCuNbSiBP alloy powder is prepared by air-spraying and atomizing method, and the amorphous nanocrystalline FeCuNbSiBP alloy powder is prepared by using air-spraying and cooling atomization method, and the amorphous nanocrystalline FeCuNbSiBP alloy powder has good spherical shape, high tap density and powder With good dispersion and low powder oxygen content, magnetic ring inductors are prepared by coating silane coupling agent and silicone resin.
The spherical and density of amorphous nanocrystalline soft magnetic alloy powder has been improved, and the powder dispersion and oxygen content are improved. The prepared magnetic ring inductor has excellent DC superposition characteristics, high frequency and low loss, and strong breakdown resistance. , comprehensive soft magnetic properties with high magnetic permeability.
Smart Images

Figure CN111968821B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of alloy materials, and in particular to a soft magnetic alloy powder and a preparation method thereof, a magnetic ring inductor and a preparation method thereof. Background Art
[0002] As the electronic market places higher and higher demands on high frequency, light weight, miniaturization and high performance of components, amorphous nanocrystalline dual-phase composite soft magnetic alloy materials with fine and uniform crystalline phases (usually less than 50nm) are gaining increasing attention. This alloy can usually be obtained by crystallization heat treatment of amorphous materials, that is, firstly, an amorphous precursor is made by melt quenching method, and then it is obtained after crystallization annealing at an appropriate temperature. The typical microstructure of Fe-based nanocrystalline soft magnetic materials is composed of an amorphous phase matrix and an α-Fe(Si) nanocrystalline phase dispersed thereon. The fine nanocrystalline grains are evenly distributed on the amorphous matrix, which makes the alloy show better comprehensive properties than polycrystalline materials or amorphous materials, such as higher strength, specific heat, saturation magnetic induction intensity, magnetic permeability, good plastic deformation ability and stability, as well as lower coercivity and loss.
[0003] For soft magnetic composite materials, once the basic element, i.e. the alloy composition of the powder, is selected, the magnetic permeability and loss of the soft magnetic composite material are mainly related to the morphology, particle size, coating process and heat treatment conditions of the magnetic powder itself. At present, the powder used to prepare amorphous nanocrystalline magnetic powder cores is mostly derived from the crushing of strip-shaped amorphous materials. Due to the sharp edges of this type of powder, it is easy to pierce the insulating layer during the pressing process of the powder core, resulting in a sharp deterioration of the soft magnetic properties.
[0004] For example, Chinese patent CN104934179B discloses an iron-based nanocrystalline soft magnetic alloy with strong amorphous forming ability and a preparation method thereof. The alloy expression is FexSiaBbPcNbdCue, in which x, a, b, c, d and e respectively represent the atomic percentage content of each corresponding component and satisfy the following conditions: 0.5≤a≤12, 0.5≤b<5, 0.5≤c≤12, 0.1≤d≤3, 0.1≤e≤3, 70≤x≤85, x+a+b+c+d+e=100%. The preparation process is to crush the master alloy ingot, melt the crushed small pieces of master alloy ingot into molten steel, and then use a single roller method, a casting method or an atomization method to prepare an Fe-based amorphous alloy material of a corresponding shape. Such powder has sharp edges, which is not conducive to later pressing. Summary of the invention
[0005] Aiming at the problem that the soft magnetic composite materials in the prior art are easy to puncture the insulating layer during the powder core pressing process, resulting in a sharp deterioration of the soft magnetic properties, the present invention adopts an air-spray water-cooled atomization method to prepare an amorphous powder precursor with an alloy component of FeCuNbSiBP, and combines the corresponding heat treatment process to perform crystallization annealing on the amorphous alloy precursor. The prepared amorphous nanocrystalline FeCuNbSiBP alloy powder has the characteristics of good sphericity, high tap density, good powder dispersibility, and low powder oxygen content, in order to provide an industrial demonstration for the large-scale production of iron-based amorphous nanocrystalline magnetic toroidal inductors. The specific technical scheme is as follows:
[0006] A method for preparing amorphous nano soft magnetic alloy powder. The obtained alloy powder has the following components in mass percentage: 6-9% Si, 1-2.5% B, 1-3% Cu, 4-7% Nb, 0.5-2% P, and 82-87.5% Fe.
[0007] Preferably, the alloy powder obtained has the following components by mass percentage: 6.5% Si, 1.7% B, 1.5% Cu, 5.8% Nb, 0.5% P, and the rest is Fe.
[0008] Preferably, the method comprises the following steps:
[0009] Step 1: Alloy smelting: prepare the ingredients according to the alloy composition, select industrial pure iron, pure copper, industrial ferroboron, single crystal silicon, ferroniobium and ferrophosphorus with a purity of 99.9% as raw materials, add the alloy raw materials into the corundum crucible to burn the steel, and the smelting adopts medium frequency induction melting;
[0010] Step 2: air-spray water-cooled atomization powder making, using a supersonic air-spray nozzle, atomizing the powder, separating the water from the powder, and vacuum drying to obtain the desired amorphous powder precursor;
[0011] Step 3: crystallization annealing treatment, using high-purity hydrogen with a dew point of -60°C as a protective atmosphere, performing crystallization annealing treatment on the atomized amorphous powder at 500-600°C for 60-90 minutes to obtain amorphous / nanocrystalline soft magnetic alloy powder;
[0012] Step 4: Powder classification and screening, using airflow classification to control powder particle size and distribution, and control the powder laser particle size D50: 13-17μm.
[0013] Step 5: Batch processing to obtain the required amorphous nano soft magnetic alloy powder.
[0014] Preferably, in step 2, an annular supersonic gas atomization nozzle is used, the inner diameter of the tundish leakage tube is 5.0-6.0 mm, and the atomization pressure is 6-8 MPa.
[0015] Preferably, the annular hole type supersonic aerosol nozzle is of model HK-03.
[0016] Preferably, in step one, the smelting power is controlled to be 200-300KW, the smelting time is 60.0-80.0 minutes, and when the molten steel temperature reaches 1500-1520°C, the power is reduced to 100-150KW, and the molten steel is slag-deoxidized with appropriate amounts of silicon calcium and lime. The process lasts for 10.0-15.0 minutes, and then the slag is cleaned and the steel is poured.
[0017] Preferably, in step 4, the powder laser particle size D50 is 13-17 μm, the powder oxygen content is ≤0.1 wt%, and the powder tap density is ≥4.5 g / cm3.
[0018] The invention also provides an amorphous nano soft magnetic alloy powder, which is prepared by the above preparation method.
[0019] The present invention also provides a method for preparing a magnetic ring inductor, comprising the following steps:
[0020] Step 1: Use 1wt% KH-550 silane coupling agent and 2wt% DC-805 silicone resin to coat the above-mentioned amorphous nano soft magnetic alloy powder, granulate it on a granulator to obtain particles with a fineness of 40 mesh, and bake it at 100°C for 1h;
[0021] Step 2: Take 27 g of the granulated powder obtained after drying in step 1, maintain the pressure at 1200 MPa for 3 seconds, and cold press to prepare the required magnetic ring inductor.
[0022] The present invention also provides a magnetic ring inductor, which is prepared by the above preparation method, and its specifications are outer diameter Φ27mm×inner diameter Φ14.5mm; under the conditions of f=100kHz and 1V, the magnetic ring inductor has an inductance value Ls≥60μH, a magnetic permeability μ≥50, and a loss Ps≤500kW / m 3 .
[0023] The composition of amorphous nanocrystalline alloys mainly includes ferromagnetic elements, such as Fe, Co, Ni, etc.; metalloid elements that improve the amorphous forming ability and thermal stability, such as Si, B, P, etc., and precious metal elements that provide positions for nanocrystalline nuclei, such as Cu, Ag, etc., and non-magnetic transition metal elements that improve the amorphous forming ability and hinder the growth of nanocrystalline, such as Nb, Zr, V, etc. The types and contents of various alloying elements have a great influence on the amorphous forming ability, crystallization process, microstructure and final magnetic properties of nanocrystalline alloys.
[0024] Si and B are both elements that improve the amorphous forming ability and thermal stability of alloys. Both have a large atomic size difference with Fe, which makes the alloy stacking more dense, thereby inhibiting nucleation and facilitating amorphous formation. Si is an important amorphizing element. Too high a content will reduce the saturation magnetic induction intensity of the alloy, and too low a content will make it difficult to form amorphous. In addition, Si is also the basic constituent element of the nanocrystalline α-Fe (Si) phase. The B element is characterized by a small atomic radius and few outer electrons, which is very beneficial for the formation of amorphous alloys. It is a constituent element of almost all nanocrystalline soft magnetic alloys. In addition, the addition of P reduces the melting point of the alloy and also has the effect of improving the thermal stability of amorphous alloys.
[0025] According to the requirements of the microstructure of nanocrystalline alloys, a small amount of Cu and Nb elements are added to the FeSiBP alloy to obtain the FeCuNbSiBP alloy. The solid solubility of Cu element in the Fe matrix is very small, and it is easy to separate from the matrix in the initial crystallization stage to form a Cu element-rich phase region, which provides a nucleation position during the crystallization process of the nanocrystalline alloy, and then hinders the further growth of grains around the α-Fe(Si) phase, reducing the size of nanocrystalline grains. Nb is also a key element in the formation of iron-based nanocrystalline alloys. The addition of Nb not only improves the ability to form iron-based amorphous, but also has a large atomic radius and slow diffusion. During the formation of nanocrystals, other elements form a structure that inhibits the precipitation of the primary crystal phase, and also prevents the growth of α-Fe(Si) phase grains.
[0026] The mechanism of air-spray water-cooled atomization powder making is that under atmospheric environment, the molten steel is poured into the insulation tundish through the medium frequency furnace, and then flows into the atomization area through the leakage hole at the bottom of the tundish. In this process, the molten steel is impacted by the supersonic airflow passing through the nozzle, and is atomized and broken into a large number of fine metal droplets. The droplets form spheres under the action of surface tension during the flight and sedimentation process, and finally fall into the water in the powder collecting tank to cool and solidify into spherical powder particles.
[0027] Amorphous powder crystallization annealing treatment: The amorphous powder is heated to a predetermined temperature (this temperature is higher than the initial crystallization temperature T X1 And below the second crystallization temperature T X2 , and slightly higher than T X1 ), keep the temperature for a period of time, the powder completes the transformation from amorphous state to amorphous / nanocrystalline composite dual-phase structure, and then furnace-cooled or air-cooled to obtain FeCuNbSiBP amorphous / nanocrystalline powder.
[0028] The parameters of amorphous nanocrystalline soft magnetic alloy powder used in magnetic ring inductors, such as powder particle size, morphology, chemical composition, and phase structure, are crucial. The particle size distribution is reasonable, the sphericity is good, and the surface is smooth. The compaction density of the prepared magnetic ring inductor is high; and the atomized amorphous powder obtains an "amorphous + nanocrystalline" dual-phase structure with good soft magnetic properties through crystallization annealing. The prepared inductor has excellent DC superposition characteristics, high frequency and low loss, strong breakdown resistance, high magnetic permeability and other excellent comprehensive soft magnetic properties.
[0029] The beneficial effects produced by the technical solution of the present invention are as follows:
[0030] (1) Through medium frequency induction melting, gas spray water cooling atomization, combined with subsequent water-powder separation, vacuum drying, crystallization annealing, powder classification and screening, the powder prepared has the characteristics of good sphericity, low oxygen content and reasonable particle size distribution.
[0031] (2) Taking into account the performance requirements such as sphericity, tap density and powder dispersibility, the proportion of industrial pure iron, pure copper, industrial ferroboron, single crystal silicon, ferroniobium and ferrophosphorus is reasonably set. After smelting, the gas spray water cooling atomization process is adopted. The molten steel is impacted by the supersonic airflow passing through the nozzle and atomized and broken into a large number of fine metal droplets. The droplets form a sphere under the action of surface tension during the flight and sedimentation process, and finally fall into the water of the powder collecting tank to cool and solidify into spherical powder particles; by designing the nozzle structure, the inner diameter of the tundish leakage tube and the atomization pressure in the gas spray water cooling atomization process, the molten steel can be quickly and evenly atomized and broken during the supersonic airflow impact process, and the powder formed by cooling in the powder collecting tank has good sphericity, low oxygen content and reasonable particle size distribution. After testing, the powder laser particle size is D50: 13-17μm, the powder oxygen content is ≤0.1wt%, and the powder tap density is ≥4.5g / cm 3 .
[0032] (3) KH-550 silane coupling agent and DC-805 silicone resin are used to coat amorphous nanocrystalline soft magnetic alloy powder and granulate it, and then it is pressed into a ring-shaped magnetic ring inductor. The pressing process is controlled at a pressure of 1200MPa for 3s to obtain a magnetic ring inductor. The inductance value Ls of the magnetic ring inductor is tested under the conditions of f=100kHz and 1V using a TH2816B / TH2826 LCR tester. The loss value of the magnetic ring inductor is tested under the conditions of Bm=100T and f=100kHz using a MATS-2010SA soft magnetic alloy AC measuring device. It can be seen that the inductance value Ls of the magnetic ring inductor is ≥60μH, the magnetic permeability μ is ≥50, and the loss Ps is ≤500kW / m 3 .
[0033] (4) FeCuNbSiBP amorphous nanocrystalline soft magnetic alloy powder is prepared by air spray water cooling atomization powder making process, which better ensures that the prepared soft magnetic alloy powder has good sphericity, high tap density, good powder dispersibility, and low powder oxygen content. The prepared magnetic ring inductor has excellent DC superposition characteristics, high frequency and low loss, strong breakdown resistance, and high magnetic permeability. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1 This is the XRD diffraction pattern of the metal powder prepared in Example 1 of the present invention;
[0036] Figure 2 This is the SEM morphology of the metal powder prepared in Example 1 of the present invention;
[0037] Figure 3 This is the SEM morphology of the metal powder prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0039] In this embodiment, an amorphous powder precursor having an alloy component of FeCuNbSiBP is prepared by air spray water cooling atomization, and the amorphous alloy precursor is subjected to crystallization annealing treatment in combination with a corresponding heat treatment process. The obtained amorphous nanocrystalline FeCuNbSiBP alloy powder has the characteristics of good sphericity, high tap density, good powder dispersibility, and low powder oxygen content.
[0040] A method for preparing amorphous nano soft magnetic alloy powder, wherein the obtained alloy powder components are as follows: 6-9% Si, 1-2.5% B, 1-3% Cu, 4-7% Nb, 0.5-2% P, 82-87.5% Fe in terms of mass percentage. The specific steps are as follows:
[0041] Step 1: Alloy smelting, according to the alloy composition, the ingredients are prepared, and industrial pure iron, pure copper, industrial ferroboron, single crystal silicon, ferroniobium and ferrophosphorus with a purity of 99.9% are selected as raw materials. The alloy raw materials are added to the corundum crucible, and the smelting power is controlled to be 200-300KW, and the smelting time is 60.0-80.0 minutes. When the temperature of the molten steel reaches 1500-1520℃, the power is reduced to 100-150KW, and the molten steel is slag-deoxidized with appropriate amounts of silicon calcium and lime. The process takes 10.0-15.0 minutes, and then the slag is cleaned and the steel is poured. The smelting adopts medium frequency induction melting.
[0042] Step 2: air-spray water-cooled atomization powder making, using HK-03 type annular hole supersonic gas atomization nozzle, the inner diameter of the tundish leakage tube is 5.0-6.0mm, the atomization pressure is 6-8MPa, the atomized powder is separated by water and powder, and vacuum dried to obtain the desired amorphous powder precursor;
[0043] Step 3: crystallization annealing treatment, using high-purity hydrogen with a dew point of -60°C as a protective atmosphere, performing crystallization annealing treatment on the atomized amorphous powder at 500-600°C for 60-90 minutes to obtain amorphous / nanocrystalline soft magnetic alloy powder;
[0044] Step 4: Powder classification and screening, use airflow classification to control powder particle size and distribution, control powder laser particle size D50: 13-17μm. Powder laser particle size D50: 13-17μm, powder oxygen content ≤ 0.1wt%, powder tap density ≥ 4.5g / cm 3 .
[0045] Step 5: Batch processing to obtain the required amorphous nano soft magnetic alloy powder.
[0046] As a preferred embodiment, the alloy powder obtained has the following components by mass percentage: 6.5% Si, 1.7% B, 1.5% Cu, 5.8% Nb, 0.5% P, and the rest is Fe.
[0047] This embodiment also provides an amorphous nano soft magnetic alloy powder, which is prepared by the above preparation method.
[0048] This embodiment also provides a method for preparing a magnetic ring inductor, which is characterized by comprising the following steps:
[0049] Step 1: Use 1wt% KH-550 silane coupling agent and 2wt% DC-805 silicone resin to coat the above-mentioned amorphous nano soft magnetic alloy powder, granulate it on a granulator to obtain particles with a fineness of 40 mesh, and bake it at 100°C for 1h;
[0050] Step 2: Take 27 g of the granulated powder obtained after drying in step 1, maintain the pressure at 1200 MPa for 3 seconds, and cold press to prepare the required magnetic ring inductor.
[0051] This embodiment also provides a magnetic ring inductor, which is prepared by the above preparation method, and its specifications are outer diameter Φ27mm×inner diameter Φ14.5mm; f=100kHz, 1V condition, magnetic ring inductor inductance value Ls≥60μH, magnetic permeability μ≥50, loss Ps≤500kW / m 3 .
[0052] The beneficial effects of the powder and the toroidal inductor obtained by adopting the technical solution of this embodiment will be further described below through several groups of examples and comparative examples.
[0053] Embodiment 1:
[0054] The preparation method of amorphous nano soft magnetic alloy powder in this embodiment comprises the following specific steps:
[0055] Step 1: Alloy smelting, the alloy powder composition is calculated by mass percentage: 6.5% Si, 1.7% B, 1.5% Cu, 5.8% Nb, 0.5% P, and the rest is Fe. The ingredients are prepared according to the alloy composition, and industrial pure iron, pure copper, industrial ferroboron, single crystal silicon, ferroniobium and ferrophosphorus with a purity of 99.9% are selected as raw materials. The alloy raw materials are added to the corundum crucible, and the smelting power is controlled to 250KW. The smelting time is 70 minutes. When the temperature of the molten steel reaches 1500℃, the power is reduced to 120KW, and the molten steel is slag-deoxidized with appropriate amounts of silicon calcium and lime. The process takes 10 minutes, and then the slag is cleaned and the steel is poured. The smelting adopts medium frequency induction melting.
[0056] Step 2: air-spray water-cooled atomization powder making, using HK-03 type annular hole supersonic gas atomization nozzle, the inner diameter of the tundish leakage tube is 5.5mm, the atomization pressure is 6MPa, the atomized powder is separated by water and powder, and vacuum dried to obtain the desired amorphous powder precursor;
[0057] Step 3: crystallization annealing treatment, using high-purity hydrogen with a dew point of -60°C as a protective atmosphere, and performing crystallization annealing treatment on the atomized amorphous powder at 500°C for 60 minutes to obtain amorphous / nanocrystalline soft magnetic alloy powder;
[0058] Step 4: Powder classification and screening, use airflow classification to control powder particle size and distribution, control powder laser particle size D50: 13-17μm. Powder laser particle size D50: 13-17μm, powder oxygen content ≤ 0.1wt%, powder tap density ≥ 4.5g / cm 3 .
[0059] Step 5: Batch processing to obtain the required amorphous nano soft magnetic alloy powder.
[0060] Embodiment 2:
[0061] The preparation method of amorphous nano soft magnetic alloy powder in this embodiment comprises the following specific steps:
[0062] Step 1: Alloy smelting, the alloy powder composition is calculated by mass percentage: 7% Si, 2.1% B, 1.5% Cu, 5.8% Nb, 0.2% P, and the rest is Fe. The ingredients are prepared according to the alloy composition, and industrial pure iron, pure copper, industrial ferroboron, single crystal silicon, ferroniobium and ferrophosphorus with a purity of 99.9% are selected as raw materials. The alloy raw materials are added to the corundum crucible, and the smelting power is controlled to 200KW. The smelting time is 60 minutes. When the temperature of the molten steel reaches 1520℃, the power is reduced to 100KW, and the molten steel is slag-deoxidized with appropriate amounts of silicon calcium and lime. The process takes 15 minutes, and then the slag is cleaned and the steel is poured. The smelting adopts medium frequency induction melting.
[0063] Step 2: air-spray water-cooled atomization powder making, using HK-03 type annular hole supersonic gas atomization nozzle, the inner diameter of the tundish leakage tube is 5.5mm, the atomization pressure is 6MPa, the atomized powder is separated by water and powder, and vacuum dried to obtain the desired amorphous powder precursor;
[0064] Step 3: crystallization annealing treatment, using high-purity hydrogen with a dew point of -60°C as a protective atmosphere, and performing crystallization annealing treatment on the atomized amorphous powder at 500°C for 60 minutes to obtain amorphous / nanocrystalline soft magnetic alloy powder;
[0065] Step 4: Powder classification and screening, use airflow classification to control powder particle size and distribution, control powder laser particle size D50: 13-17μm. Powder laser particle size D50: 13-17μm, powder oxygen content ≤ 0.1wt%, powder tap density ≥ 4.5g / cm 3 .
[0066] Step 5: Batch processing to obtain the required amorphous nano soft magnetic alloy powder.
[0067] Embodiment three:
[0068] The preparation method of amorphous nano soft magnetic alloy powder in this embodiment comprises the following specific steps:
[0069] Step 1: Alloy smelting. The alloy powder components are as follows: 6.5% Si, 1.7% B, 1.5% Cu, 5.8% Nb, 0.5% P, and the rest is Fe. The ingredients are prepared according to the alloy composition. Industrial pure iron, pure copper, industrial ferroboron, single crystal silicon, ferroniobium and ferrophosphorus with a purity of 99.9% are selected as raw materials. The alloy raw materials are added to the corundum crucible. The smelting power is controlled to 230KW, and the smelting time is 80 minutes. When the temperature of the molten steel reaches 1510℃, the power is reduced to 150KW. The molten steel is slag-forming and deoxidized with appropriate amounts of silicon calcium and lime. The process takes 12 minutes. Then the slag is removed and the steel is poured. The smelting adopts medium frequency induction melting.
[0070] Step 2: air-spray water-cooled atomization powder making, using HK-03 type annular hole supersonic gas atomization nozzle, the inner diameter of the tundish leakage tube is 5.5mm, the atomization pressure is 8MPa, the atomized powder is separated by water and powder, and vacuum dried to obtain the desired amorphous powder precursor;
[0071] Step 3: crystallization annealing treatment, using high-purity hydrogen with a dew point of -60°C as a protective atmosphere, and performing crystallization annealing treatment on the atomized amorphous powder at 500°C for 60 minutes to obtain amorphous / nanocrystalline soft magnetic alloy powder;
[0072] Step 4: Powder classification and screening, use airflow classification to control powder particle size and distribution, control powder laser particle size D50: 13-17μm. Powder laser particle size D50: 13-17μm, powder oxygen content ≤ 0.1wt%, powder tap density ≥ 4.5g / cm 3 .
[0073] Step 5: Batch processing to obtain the required amorphous nano soft magnetic alloy powder.
[0074] Embodiment 4:
[0075] The preparation method of amorphous nano soft magnetic alloy powder in this embodiment comprises the following specific steps:
[0076] Step 1: Alloy smelting, the alloy powder composition is calculated by mass percentage: 6.5% Si, 1.7% B, 1.5% Cu, 5.8% Nb, 0.5% P, and the rest is Fe. The ingredients are prepared according to the alloy composition, and industrial pure iron, pure copper, industrial ferroboron, single crystal silicon, ferroniobium and ferrophosphorus with a purity of 99.9% are selected as raw materials. The alloy raw materials are added to the corundum crucible, and the smelting power is controlled to 300KW. The smelting time is 60 minutes. When the temperature of the molten steel reaches 1520℃, the power is reduced to 110KW, and the molten steel is slag-deoxidized with appropriate amounts of silicon calcium and lime. The process takes 12 minutes, and then the slag is cleaned and the steel is poured. The smelting adopts medium frequency induction melting.
[0077] Step 2: air-spray water-cooled atomization powder making, using HK-03 type annular hole supersonic gas atomization nozzle, the inner diameter of the tundish leakage tube is 5.5mm, the atomization pressure is 6MPa, the atomized powder is separated by water and powder, and vacuum dried to obtain the desired amorphous powder precursor;
[0078] Step 3: crystallization annealing treatment, using high-purity hydrogen with a dew point of -60°C as a protective atmosphere, and performing crystallization annealing treatment on the atomized amorphous powder at 560°C for 80 minutes to obtain amorphous / nanocrystalline soft magnetic alloy powder;
[0079] Step 4: Powder classification and screening, use airflow classification to control powder particle size and distribution, control powder laser particle size D50: 13-17μm. Powder laser particle size D50: 13-17μm, powder oxygen content ≤ 0.1wt%, powder tap density ≥ 4.5g / cm 3 .
[0080] Step 5: Batch processing to obtain the required amorphous nano soft magnetic alloy powder.
[0081] Comparative Example 1:
[0082] The preparation method of the amorphous nano soft magnetic alloy powder in this comparative example comprises the following specific steps:
[0083] Step 1: Alloy smelting, the alloy powder composition is calculated by mass percentage: 6.5% Si, 1.7% B, 1.5% Cu, 5.8% Nb, 0.5% P, and the rest is Fe. The ingredients are prepared according to the alloy composition, and industrial pure iron, pure copper, industrial ferroboron, single crystal silicon, ferroniobium and ferrophosphorus with a purity of 99.9% are selected as raw materials. The alloy raw materials are added to the corundum crucible, and the smelting power is controlled to 250KW. The smelting time is 70 minutes. When the temperature of the molten steel reaches 1500℃, the power is reduced to 120KW, and the molten steel is slag-deoxidized with appropriate amounts of silicon calcium and lime. The process takes 10 minutes, and then the slag is cleaned and the steel is poured. The smelting adopts medium frequency induction melting.
[0084] Step 2: Water-gas combined with water atomization powder making, using nitrogen as the process protective atmosphere, the nitrogen flow rate is 25.0m 3 / h; the atomization process uses 35° / 25° main and auxiliary spray plates, double V-shaped nozzles, the leakage size of the bottom of the molten steel ladle is 5.0mm, the atomization pressure is 100MPa, and the atomization water flow rate is 120L / min; the powder obtained by atomization is separated by water and powder and vacuum dried to obtain the desired amorphous powder precursor;
[0085] Step 3: crystallization annealing treatment, using high-purity hydrogen with a dew point of -60°C as a protective atmosphere, and performing crystallization annealing treatment on the atomized amorphous powder at 500°C for 60 minutes to obtain amorphous / nanocrystalline soft magnetic alloy powder;
[0086] Step 4: Powder classification and screening, use airflow classification to control powder particle size and distribution, control powder laser particle size D50: 13-17μm. Powder laser particle size D50: 13-17μm, powder oxygen content ≤ 0.1wt%, powder tap density ≥ 4.5g / cm 3 .
[0087] Step 5: Batch processing to obtain the required amorphous nano soft magnetic alloy powder.
[0088] Comparative Example 2:
[0089] The preparation method of the amorphous nano soft magnetic alloy powder in this comparative example comprises the following specific steps:
[0090] Step 1: Alloy smelting, the alloy powder composition is calculated by mass percentage: 6.5% Si, 1.7% B, 1.5% Cu, 5.8% Nb, 0.5% P, and the rest is Fe. The ingredients are prepared according to the alloy composition, and industrial pure iron, pure copper, industrial ferroboron, single crystal silicon, ferroniobium and ferrophosphorus with a purity of 99.9% are selected as raw materials. The alloy raw materials are added to the corundum crucible, and the smelting power is controlled to 250KW. The smelting time is 70 minutes. When the temperature of the molten steel reaches 1500℃, the power is reduced to 120KW, and the molten steel is slag-deoxidized with appropriate amounts of silicon calcium and lime. The process takes 10 minutes, and then the slag is cleaned and the steel is poured. The smelting adopts medium frequency induction melting.
[0091] Step 2: air-spray water-cooled atomization powder making, using HK-03 type annular hole supersonic air atomization nozzle, the inner diameter of the tundish leakage tube is 5.5mm, the atomization pressure is 4MPa, the atomized powder is separated by water and powder, and vacuum dried to obtain the desired amorphous powder precursor;
[0092] Step 3: crystallization annealing treatment, using high-purity hydrogen with a dew point of -60°C as a protective atmosphere, and performing crystallization annealing treatment on the atomized amorphous powder at 500°C for 60 minutes to obtain amorphous / nanocrystalline soft magnetic alloy powder;
[0093] Step 4: Powder classification and screening, use airflow classification to control powder particle size and distribution, control powder laser particle size D50: 13-17μm. Powder laser particle size D50: 13-17μm, powder oxygen content ≤ 0.1wt%, powder tap density ≥ 4.5g / cm 3 .
[0094] Step 5: Batch processing to obtain the required amorphous nano soft magnetic alloy powder.
[0095] Comparative Example 3:
[0096] The preparation method of the amorphous nano soft magnetic alloy powder in this comparative example comprises the following specific steps:
[0097] Step 1: Alloy smelting, the alloy powder composition is calculated by mass percentage: 6.5% Si, 1.7% B, 1.5% Cu, 5.8% Nb, 0.5% P, and the rest is Fe. The ingredients are prepared according to the alloy composition, and industrial pure iron, pure copper, industrial ferroboron, single crystal silicon, ferroniobium and ferrophosphorus with a purity of 99.9% are selected as raw materials. The alloy raw materials are added to the corundum crucible, and the smelting power is controlled to 250KW. The smelting time is 70 minutes. When the temperature of the molten steel reaches 1500℃, the power is reduced to 120KW, and the molten steel is slag-deoxidized with appropriate amounts of silicon calcium and lime. The process takes 10 minutes, and then the slag is cleaned and the steel is poured. The smelting adopts medium frequency induction melting.
[0098] Step 2: air-spray water-cooled atomization powder making, using HK-03 type annular hole supersonic air atomization nozzle, the inner diameter of the tundish leakage tube is 5.5mm, the atomization pressure is 10MPa, the atomized powder is separated by water and powder, and vacuum dried to obtain the desired amorphous powder precursor;
[0099] Step 3: crystallization annealing treatment, using high-purity hydrogen with a dew point of -60°C as a protective atmosphere, and performing crystallization annealing treatment on the atomized amorphous powder at 500°C for 60 minutes to obtain amorphous / nanocrystalline soft magnetic alloy powder;
[0100] Step 4: Powder classification and screening, use airflow classification to control powder particle size and distribution, control powder laser particle size D50: 13-17μm. Powder laser particle size D50: 13-17μm, powder oxygen content ≤ 0.1wt%, powder tap density ≥ 4.5g / cm 3 .
[0101] Step 5: Batch processing to obtain the required amorphous nano soft magnetic alloy powder.
[0102] Comparative Example 4:
[0103] The preparation method of the amorphous nano soft magnetic alloy powder in this comparative example comprises the following specific steps:
[0104] Step 1: Alloy smelting, the alloy powder composition is calculated by mass percentage: 6.5% Si, 1.7% B, 1.5% Cu, 5.8% Nb, 0.5% P, and the rest is Fe. The ingredients are prepared according to the alloy composition, and industrial pure iron, pure copper, industrial ferroboron, single crystal silicon, ferroniobium and ferrophosphorus with a purity of 99.9% are selected as raw materials. The alloy raw materials are added to the corundum crucible, and the smelting power is controlled to 250KW. The smelting time is 70 minutes. When the temperature of the molten steel reaches 1500℃, the power is reduced to 120KW, and the molten steel is slag-deoxidized with appropriate amounts of silicon calcium and lime. The process takes 10 minutes, and then the slag is cleaned and the steel is poured. The smelting adopts medium frequency induction melting.
[0105] Step 2: air-spray water-cooled atomization powder making, using HK-03 type annular hole supersonic gas atomization nozzle, the inner diameter of the tundish leakage tube is 4.0mm, the atomization pressure is 6MPa, the atomized powder is separated by water and powder, and vacuum dried to obtain the desired amorphous powder precursor;
[0106] Step 3: crystallization annealing treatment, using high-purity hydrogen with a dew point of -60°C as a protective atmosphere, and performing crystallization annealing treatment on the atomized amorphous powder at 500°C for 60 minutes to obtain amorphous / nanocrystalline soft magnetic alloy powder;
[0107] Step 4: Powder classification and screening, use airflow classification to control powder particle size and distribution, control powder laser particle size D50: 13-17μm. Powder laser particle size D50: 13-17μm, powder oxygen content ≤ 0.1wt%, powder tap density ≥ 4.5g / cm 3 .
[0108] Step 5: Batch processing to obtain the required amorphous nano soft magnetic alloy powder.
[0109] Comparative Example 5:
[0110] The preparation method of the amorphous nano soft magnetic alloy powder in this comparative example comprises the following specific steps:
[0111] Step 1: Alloy smelting, the alloy powder composition is calculated by mass percentage: 6.5% Si, 1.7% B, 1.5% Cu, 5.8% Nb, 0.5% P, and the rest is Fe. The ingredients are prepared according to the alloy composition, and industrial pure iron, pure copper, industrial ferroboron, single crystal silicon, ferroniobium and ferrophosphorus with a purity of 99.9% are selected as raw materials. The alloy raw materials are added to the corundum crucible, and the smelting power is controlled to 250KW. The smelting time is 70 minutes. When the temperature of the molten steel reaches 1500℃, the power is reduced to 120KW, and the molten steel is slag-deoxidized with appropriate amounts of silicon calcium and lime. The process takes 10 minutes, and then the slag is cleaned and the steel is poured. The smelting adopts medium frequency induction melting.
[0112] Step 2: air-spray water-cooled atomization powder making, using HK-03 type annular hole supersonic gas atomization nozzle, the inner diameter of the tundish leakage tube is 7.0mm, the atomization pressure is 6MPa, the atomized powder is separated by water and powder, and vacuum dried to obtain the desired amorphous powder precursor;
[0113] Step 3: crystallization annealing treatment, using high-purity hydrogen with a dew point of -60°C as a protective atmosphere, and performing crystallization annealing treatment on the atomized amorphous powder at 500°C for 60 minutes to obtain amorphous / nanocrystalline soft magnetic alloy powder;
[0114] Step 4: Powder classification and screening, use airflow classification to control powder particle size and distribution, control powder laser particle size D50: 13-17μm. Powder laser particle size D50: 13-17μm, powder oxygen content ≤ 0.1wt%, powder tap density ≥ 4.5g / cm 3 .
[0115] Step 5: Batch processing to obtain the required amorphous nano soft magnetic alloy powder.
[0116] Comparative Example 6:
[0117] The preparation method of the amorphous nano soft magnetic alloy powder in this comparative example comprises the following specific steps:
[0118] Step 1: Alloy smelting, the alloy powder composition is 6.5% Si, 1.7% B, 0.5% P, and the rest is Fe. The ingredients are prepared according to the alloy composition, and industrial pure iron, industrial ferroboron, single crystal silicon, and ferrophosphorus with a purity of 99.9% are selected as raw materials. The alloy raw materials are added to the corundum crucible, and the smelting power is controlled to 250KW. The smelting time is 70 minutes. When the temperature of the molten steel reaches 1500℃, the power is reduced to 120KW, and the molten steel is slag-deoxidized with appropriate amounts of silicon calcium and lime. The process takes 10 minutes, and then the slag is cleaned and the steel is poured. The smelting adopts medium frequency induction melting.
[0119] Step 2: air-spray water-cooled atomization powder making, using HK-03 type annular hole supersonic gas atomization nozzle, the inner diameter of the tundish leakage tube is 5.5mm, the atomization pressure is 6MPa, the atomized powder is separated by water and powder, and vacuum dried to obtain the desired amorphous powder precursor;
[0120] Step 3: crystallization annealing treatment, using high-purity hydrogen with a dew point of -60°C as a protective atmosphere, and performing crystallization annealing treatment on the atomized amorphous powder at 500°C for 60 minutes to obtain amorphous / nanocrystalline soft magnetic alloy powder;
[0121] Step 4: Powder classification and screening, use airflow classification to control powder particle size and distribution, control powder laser particle size D50: 13-17μm. Powder laser particle size D50: 13-17μm, powder oxygen content ≤ 0.1wt%, powder tap density ≥ 4.5g / cm 3 .
[0122] Step 5: Batch processing to obtain the required amorphous nano soft magnetic alloy powder.
[0123] The powders obtained in the above four groups of embodiments and six groups of comparative examples are used to prepare magnetic ring inductors, and the specific process is as follows:
[0124] Step 1: Use 1wt% KH-550 silane coupling agent and 2wt% DC-805 silicone resin to coat the above-mentioned amorphous nano soft magnetic alloy powder, granulate it on a granulator to obtain particles with a fineness of 40 mesh, and bake it at 100°C for 1h;
[0125] Step 2: Take 27 g of the granulated powder obtained after drying in step 1, maintain the pressure for 3 seconds under a pressure of 1200 MPa, and cold press to prepare the required magnetic ring inductor with a specification of outer diameter Φ27 mm×inner diameter Φ14.5 mm.
[0126] The powder obtained in Example 1 and conventional amorphous powder were subjected to XRD diffraction to form an XRD diffraction pattern, such as Figure 1 As shown in the figure, the powder in Example 1 is the diffraction pattern located at the top; the conventional amorphous powder is the diffraction pattern located at the bottom. Figure 2 and Figure 3 The figures show the SEM morphologies of the metal powders in Example 1 and Comparative Example 1, respectively. It can be seen that the alloy powder obtained in Example 1 has good sphericity, high tap density and good powder dispersibility.
[0127] The powders obtained from the above four groups of embodiments and six groups of comparative examples were tested for powder laser particle size, oxygen content, and tap density. The obtained magnetic ring inductors were tested for inductance value Ls at f = 100kHz and 1V using TH2816B / TH2826 LCR tester, and the loss value of magnetic ring inductors was tested at Bm = 100T and f = 100kHz using MATS-2010SA soft magnetic alloy AC measuring device. The specific data are as follows:
[0128] Table 1 Test data of powder and magnetic ring inductors obtained in each group of embodiments and comparative examples
[0129]
[0130] As shown in Table 1, the air-spray water-cooled atomization powder making process is adopted, and the inner diameter of the tundish leakage tube and the atomization pressure are optimized to better ensure the reasonable particle size distribution of the prepared soft magnetic alloy powder, good powder sphericity, high tap density, low oxygen content, etc. The prepared magnetic ring inductor product has good pressing performance, high inductance value and magnetic permeability, and low loss. The addition of a small amount of Cu and Nb elements plays a vital role in the nucleation of nanocrystals, inhibiting the precipitation of the primary crystal phase and preventing the growth of α-Fe(Si) phase grains during the alloy crystallization process, making the amorphous nanocrystalline material have better comprehensive performance.
[0131] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing amorphous nano soft magnetic alloy powder, characterized in that: The obtained alloy powder has the following components in mass percentage: 6-9% Si, 1-2.5% B, 1-3% Cu, 4-7% Nb, 0.5-2% P, 82-87.5% Fe; Step 1: Alloy smelting, prepare the ingredients according to the alloy composition, select industrial pure iron, pure copper, industrial ferroboron, single crystal silicon, ferroniobium and ferrophosphorus with a purity of 99.9% as raw materials, add the alloy raw materials into the corundum crucible to burn steel; control the smelting power to 200-300KW, the smelting time is 60.0-80.0 minutes, when the temperature of the molten steel reaches 1500-1520℃, reduce the power to 100-150KW, use appropriate amount of silicon calcium and lime to slag and deoxidize the molten steel, the process time is 10.0-15.0 minutes, then remove the slag and pour the steel; Step 2: air-spray water-cooled atomization powder making, using HK-03 type annular hole supersonic gas atomization nozzle, the inner diameter of the tundish leakage tube is 5.0-6.0mm, the atomization pressure is 6-8MPa, the atomized powder is separated by water and powder, and vacuum dried to obtain the desired amorphous powder precursor; Step 3: crystallization annealing treatment, using high-purity hydrogen with a dew point of -60°C as a protective atmosphere, performing crystallization annealing treatment on the atomized amorphous powder at 500-600°C for 60-90 minutes to obtain amorphous / nanocrystalline soft magnetic alloy powder; Step 4: Powder classification and screening, using airflow classification to control powder particle size and distribution, control powder laser particle size D50: 13-17μm, powder oxygen content ≤ 0.1wt%, powder tap density ≥ 4.5g / cm3; Step 5: Batch processing to obtain the required amorphous nano soft magnetic alloy powder.
2. The method for preparing amorphous nano soft magnetic alloy powder according to claim 1, characterized in that: The obtained alloy powder components are respectively 6.5% Si, 1.7% B, 1.5% Cu, 5.8% Nb, 0.5% P, and the rest is Fe in mass percentage.
3. An amorphous nano soft magnetic alloy powder, characterized in that: The method is prepared according to any one of claims 1 to 2.
4. A method for preparing a magnetic ring inductor, characterized in that: The steps include: Step 1: using 1wt% KH-550 silane coupling agent and 2wt% DC-805 silicone resin to coat the amorphous nano soft magnetic alloy powder as claimed in claim 3, and granulating it on a granulator to obtain particles with a fineness of 40 mesh, and baking it at 100°C for 1h; Step 2: Take 27 g of the granulated powder obtained after drying in step 1, maintain the pressure at 1200 MPa for 3 seconds, and cold press to prepare the required magnetic ring inductor.
5. A magnetic ring inductor, characterized in that: The invention is prepared by the preparation method as claimed in claim 4, and its specifications are outer diameter Φ27mm×inner diameter Φ14.5mm; under the condition of f=100kHz and 1V, the inductance value of the magnetic ring is Ls≥60μH, the magnetic permeability μ≥50, and the loss Ps≤500kW / m 3 .
